An efficient multiscale strategy to predict the evolution of the real contact area between rough surfaces. (January 2022) - Pinto Carvalho, R.; Couto Carneiro, A.M.; Andrade Pires, F.M.; Doca, T.
Abstract: An efficient and general multiscale strategy to model rough contact and determine the evolution of the real contact area is proposed, based on the splitting of the surface power spectrum. A multiplicative homogenisation scheme is developed to evaluate the contact area fraction effectively, by incorporating statistical information of the contact pressure field in the scale transitions. A strategy for separating the roughness frequencies and for generating the topography at each scale is proposed. The comparison between direct numerical simulation and the proposed multiscale strategy demonstrates the capability to predict the contact area evolution of multiscale rough topographies. The significant reduction of the computational cost endorses the applicability of the proposed multiscale framework to practical circumstances. Graphical Abstract: ga1 Highlights: Decomposition of the surface spectrum by splitting roughness on the frequency domain using new techniques. Multiplicative homogenisation that incorporates statistical information of the contact pressure field. Meticulous numerical validation by comparing the results with direct numerical simulation. Significant reduction of the computational cost while preserving the overall accuracy.